Goyang Karawang: Exploration of Woman’s Body Between Rites and Fiesta - Citra Aryandari; Gilang Muhamad Sidiq (Institut Seni Indonesia Denpasar, 2017)
This study will discuss about Goyang Karawang, which always brings eroticism of woman's body in every show. Eroticism presented through swaying hips is inseparable from the history that surrounds. The changing Karawang district (32 miles of Jakarta, Indonesia) from agriculture to industrial making the culture in this area transformed. In agriculture period, which is almost the entire population of Karawang as a farmer known as Bajidoran, is used as a fertility rite to celebrate the harvest. Swaying hips of the dancers in Bajidoran later evolved into the cultural identity of the region and then known as Goyang Karawang. In 90's Goyang Karawang was also known as a dangdut song title that described the condition of the culture. Karawang has been turned into industrial city. Bajidoran was adapted to era and is popularly known as Goyang Karawang who peddles female’s body as commodity with many text weaving. Goyang Karawang: Exploring of Woman’s Body between Rites and Fiesta is a simple article about the cultural phenomena that occurred in Karawang. Goyang Karawang existence as a cultural text cannot be separated from the study of music, history, social, gender, etc., so in the process of research and writing would be in Cultural Studies for weaving the texts which are presented. Ethnography is selected as the method of data collection, considering that this method can describe with deep cultural events.Penelitian ini akan membahas mengenai Goyang Karawang yang selalu menghadirkan erotisme tubuh perempuan dalam setiap pertunjukannya. Erotisme yang dihadirkan melalui goyangan badan tidak terlepas dari sejarah yang melingkupi. Perubahan kota dari agraris menuju industri membuat kesenian yang ada di wilayah Karawang berubah bentuk. Pada masa agraris, masa dimana hampir seluruh penduduk Karawang bermata pencarian sebagai petani dikenal kesenian Bajidoran yang digunakan sebagai ritus kesuburan dalam merayakan masa panen. Goyang penari dalam Bajidoran kemudian berkembang seiring waktu dan menjadi identitas wilayah yang kemudian dipopulerkan lewat lagu Dangdut Goyang Karawang. Kini Karawang telah berubah menjadi kota Industri, sehingga Bajidoran beradaptasi dengan jaman dan kini populer dengan Goyang Karawang yang menjajakan tubuh perempuan sebagai komoditas dengan bermacam teks yang tejalin. Goyang Karawang: Penjelajahan Tubuh Perempuan diantara Ritus dan Fiesta merupakan tulisan sederhanamengenai fenomena budaya yang terjadi di Kota Karawang. Keberadaan Goyang Karawang sebagai sebuah teks budaya tidak dapat dipisahkan dari kajian musik, sejarah, gender, sosial sehingga dalam proses penelitan dan penulisan akan digunakan Cultural Studies dalam menenun teks-teks yanghadir. Metode etnografi dipilih sebagai metode dalam proses pencarian data, mengingat metode ini dapat menggambarkan peristiwa budaya dengan mendalam.